KETERKAITAN ANTARA SARAPAN DENGAN TINGKAT KONSENTRASI BELAJAR SISWA SMA NEGERI 1 PURI MOJOKERTO - Mochammad Ivan Abdillah Putra Ginka; Sudiarno; Aliyatul Muhasshonah; Maura Endriana Sari; Nahla Marsha Niswah; Reina Marchi Rinjani; Revo Haedar Elmirza; Verra Putri Nur Azizah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
There are many factors that affect a student's ability to concentrate. One of them is breakfast. This study aimed to find out the breakfast menu of students and the impact of breakfast on concentration skills of students at SMAN 1 Puri. This study used crossectional study conducting a survey of 50 randomly selected 12th grade students of SMAN 1 Puri school. Breakfast Habits and Concentration Questionnaire Using an Online Google Form. Survey results show that SMAN 1 Puri students are accustomed to eating breakfast in science, social studies, and language classes. The breakfast menu chosen by most SMAN 1 Puri students is quite delicious: rice and the most popular drink in the morning is water. None of the students who ate rice for breakfast had low levels of concentration, while some students who ate bread for breakfast had low levels of concentration. Among the students who usually drank water for breakfast, none of them had low concentration levels. When eating breakfast, most students have a fairly high ability to concentrate, whereas when not eating breakfast, most students have a low ability to concentrate. Breakfast habits have a great impact on students' ability to concentrate at school. Realizing the importance of breakfast, families should actively seek information about healthy breakfast menus to improve their children's thinking skills. In addition, schools should implement a program to provide one gallon of drinking water to each classroom as part of hydration efforts to increase students' brain energy intake.